Somatic targeted mutation profiling of colorectal cancer precursor lesions - Wellington dos Santos; Mariana Bisarro dos Reis; Jun Porto; Ana Carolina de Carvalho; Marcus Matsushita; Gabriela Oliveira; Kari Syrjänen; Rui Manuel Reis; Denise Peixoto Guimarães (BMC, 2022)
Abstract Background Most colorectal cancers (CRC) arise from precursor lesions. This study aimed to characterize the mutation profile of colorectal cancer precursor lesions in a Brazilian population. Methods In total, 90 formalin-fixed paraffin-embedded colorectal precursor lesions, including 67 adenomas, 7 sessile serrated lesions, and 16 hyperplastic polyps, were analyzed by next-generation sequencing using a panel of 50 oncogenes and tumor suppressor genes. The genetic ancestry of the patients was estimated. Results Somatic driver mutations were identified in 66.7% of cases, including alterations in APC (32.2%), TP53 (20.0%), KRAS (18.9%), BRAF (13.3%) and EGFR (7.8%). Adenomas displayed a higher number of mutations, mainly in APC, compared to serrated polyps (73.1% vs. 47.8%, p = 0.026). Advanced adenomas had a significantly higher frequency of mutation in KRAS and a high overall mutation rate than early adenomas (92.9% vs. 59%, p = 0.006). A high degree of ancestry admixture was observed in the population studied, with a predominance of European components (mean of 73%) followed by African (mean of 11.3%). No association between genetic ancestry and type of lesions was found. The mutation profile of Brazilian colorectal precursor lesions exhibits alteration in APC, KRAS, TP53, and BRAF at different frequencies according to lesion type. Conclusions These results bestow the knowledge of CRC's biologic history and support the potential of these biomarkers for precursor lesions detection in CRC screening of the Brazilian population.